2017
DOI: 10.1103/physrevmaterials.1.015401
|View full text |Cite
|
Sign up to set email alerts
|

Combining the AFLOW GIBBS and elastic libraries to efficiently and robustly screen thermomechanical properties of solids

Abstract: Thorough characterization of the thermo-mechanical properties of materials requires difficult and time-consuming experiments. This severely limits the availability of data and is one of the main obstacles for the development of effective accelerated materials design strategies. The rapid screening of new potential materials requires highly integrated, sophisticated and robust computational approaches. We tackled the challenge by developing an automated, integrated workflow with robust error-correction within t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(116 citation statements)
references
References 134 publications
1
115
0
Order By: Relevance
“…AAPL: AutomaticAnharmonic-Phonon-Library; AGL: AFLOW-Gibbs-Library; 15 APL: Automatic-Phonon-Library; 28,35,16 QHA: quasi-harmonic approximation; 7 ACBN0: Agapito Curtarolo Buongiorno Nardelli ab-initio DFT functional; 40 AFLOWπ: A minimalist AFLOW-Python approach to high-throughput ab-initio calculations for the generation of tight-binding hamiltonians and the calculation with the ACBN0 functional. 111 …”
Section: Acronyms In the Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…AAPL: AutomaticAnharmonic-Phonon-Library; AGL: AFLOW-Gibbs-Library; 15 APL: Automatic-Phonon-Library; 28,35,16 QHA: quasi-harmonic approximation; 7 ACBN0: Agapito Curtarolo Buongiorno Nardelli ab-initio DFT functional; 40 AFLOWπ: A minimalist AFLOW-Python approach to high-throughput ab-initio calculations for the generation of tight-binding hamiltonians and the calculation with the ACBN0 functional. 111 …”
Section: Acronyms In the Frameworkmentioning
confidence: 99%
“…Similarly, classical molecular dynamics combined with Green-Kubo relations [11][12][13] is reasonably quick but requires the knowledge of specific force fields. On the contrary, frameworks based on the quasiharmonic Debye model, such as GIBBS 14 or the Automatic-Gibbs-Library (AGL), 15,16 are extremely efficient as pre-screening techniques but they lack quantitative accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…This set of materials spanned a wide range of hardness values (H Exp v = 0.2 − 96.0 GPa), and included ionic and covalently bonded crystals, as well as intermetallics. It has been demonstrated that AFLOW-AEL calculates reasonable bulk and shear moduli [29], so it should not be a surprise that the Vickers hardnesses obtained using them are in good agreement with experiment, and the predicted values reflect the variation in the results of the models themselves.…”
Section: A Macroscopic Hardness Models Coupled With Machine Learningmentioning
confidence: 81%
“…Detailed computational settings for the AFLOW-AEL [29] calculations used to determine the elastic properties are described in Ref. 66.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation